KARAKTERISTIK KEAGENAN BANK - Andika Persada Putera (Universitas Airlangga, 2014)
Rapid development of the national economy and banking external environment, such as non-bank financial institutions, capital markets, securities companies, insurance as well as the needs of the people, are causing the services and banking products also developed and varied. Banking activities not only engage in activities that are primary (core business), but also non-core business such as agency activities as Mutual Fund Sales Agent (APERD) and bancassurance. The implementation of bank agency, when the transaction is done and the position of non-bank products principals is represented by the bank as a sales agent, the principal responsibility for third-party funds invested in investment products belongs to the principal. However, all forms of relations and communications between the principal with a third party at a bank as an agent or intermediary for both parties.Keywords: bank, bank agency, investment.